Trust, Trusting and Trustworthiness in Ethical Discourse = ālāʾmāna ūālṯqa ūḥsn ālẓn fī ālḫṭāb ālāʾḫlāqī - Eggen, Nora S. (Journal of Islamic ethics, 2021)
Abstract In literary genres concerned with an ethics of character, scholars in the third through fifth/ninth through eleventh century wrote about social trust. In this article I examine the ethical thinking of four such scholars: Ibn Abī l-Dunyā (d. 281/894), al-Kharāʾiṭī (d. 327/939), al-Māwardī (d. 450/1058), and al-Ghazālī (d. 505/1111). Locating conceptualisations of the ethical concerns related to trust and mistrust, trustworthiness, trusting and misplaced trust, in a semantic field including the vocabulary of amāna, tawakkul, thiqa and ḥusn al-ẓann, I identify and discuss in this article some of these concerns, and I analyse in what ways the scholars’ respective conceptualisations of issues related to trust are similar, and how they differ from each other. While some scholars explicitly conceptualise the ethical value of trust in the concept of amāna, the juxtaposed social and spiritual aspects of the concept of amāna is more implicit with other scholars.